Attitude, practice and its associated factors towards Diabetes complications among type 2 diabetic patients at Addis Zemen District hospital, Northwest Ethiopia - Yitayeh Belsti; Yonas Akalu; Yaregal Animut (BMC, 2020)
Abstract Background This study aimed to assess the level of attitude, practices, and its associated factors towards complications of diabetes mellitus among type 2 diabetes patients. Methods An institution-based cross-sectional study was done on type 2 diabetes patients coming to the diabetes outpatient department at Addis Zemen District Hospital in Northwest Ethiopia. Interviewer-administered structured questionnaires were used to collect data from 402 patients. Multivariable logistic regression was employed to decide on factors related to practices and attitudes towards diabetes complications. AOR with 95% CI and p-value under 0.05 was considered to select significantly associated variables. Results Two-thirds of the study participants (65.2% (95% CI: 60.2, 69.4)) had a good attitude level while less than half of study participants (48.8% (95% CI: 44.0, 53.5)) had a good practice on diabetes complications. Educational status of read and write (AOR = 2.32, 95% CI(1.26, 4.27)), primary school (AOR = 4.31, 95% CI(2.06, 9.02)), high school and above (AOR = 2.79, 95% CI (1.41, 5.50)), and urban residence (AOR = 1.80, 95% CI (1.12 2.91)) were significant factors for good attitude while educational status of read and write (AOR = 1.96, 95% CI (1.06, 3.61)), and high school and above (AOR = 2.57, 95% CI (1.32, 5.02)) were associated with diabetes complication practices. Conclusions A greater proportion of diabetes patients had a relatively good attitude but poor practice towards diabetes complication preventions. Residence was a contributing variable for a good attitude while the level of education was significantly associated with both practice and attitude. The current study suggests the need for structured educational programs about diabetes complications regularly to improve patient's attitudes and practice.